Design of improved PID algorithm for position control of servo unit - Shuwang Du; Zhilin Feng; Zhiming Fang (2010 International Conference on Computer and Communication Technologies in Agriculture Engineering, 2010)
Controller is the critical component in servo systems, and the design of control algorithm is one of the most important mission. After making a study of several new type PID algorithm, according to the control unit's actual condition, the course of design and realization about this kind of improved PID algorithm is presented. Through feed-forward action ameliorative, dynamic character of the control can be achieved, also the complex control process combined separation integral PID and incomplete derivation PID, can weaken the influence of swash disturbance obviously. Experiments show that this controller can satisfy the target requirements, and also can provide a relatively good control performance and anti-jamming capability.